THE AESTHETICS OF KORI KUWADI - I Wayan Balika Ika; Putu Ari Darmastuti (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: As one of the objects of Balinese cultural heritage, it should be preserved. But in reality, Kori Kuwadi is exploited not only as a building component but also as a commodity that is traded and even exported to foreign countries. To obtain maximum profit, Kori Kuwadi is mass-produced to meet market demand. Because it is oriented towards high profits, the production process may ignore the Kori Kuwadi concept as it should. Ironic while the existence of Kori Kuwadi is widely known both by the Balinese people and the people outside Bali, because the shape, model, size, and ornament are so beautiful that they are admired, but it's a shame because there are still many people who don't know what the real name of the door is. which they are familiar with the term